2021
DOI: 10.5339/qmj.2021.1
|View full text |Cite
|
Sign up to set email alerts
|

Pneumorrhachis and pneumothorax after epidural analgesia: A case report and review

Abstract: Epidural analgesia or anesthesia is a common procedure for pain relief, especially in obstetrics. Pneumorrhachis and pneumothorax are rare complications of epidural analgesia. They are considered asymptomatic entities but have recently caused increased morbidity and mortality. As the use of epidural analgesia and anesthesia increased significantly in the last decade, clinicians must be aware of this entity. This is a case report of pneumorrhachis causing pneumothorax and pneumomediastinum leading to respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Similarly to our case, Shaik et al reported pneumorrhachis and pneumothorax in a 26-year old primi gravida which was scheduled for a cesarean section [ 10 ]. An epidural was performed prior to the procedure, again using the LOR with air technique.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly to our case, Shaik et al reported pneumorrhachis and pneumothorax in a 26-year old primi gravida which was scheduled for a cesarean section [ 10 ]. An epidural was performed prior to the procedure, again using the LOR with air technique.…”
Section: Discussionsupporting
confidence: 81%
“…In this case, pneumorrhachis and pneumomediastinum were incidentally detected on CT imaging on postoperative day two. Previous reports have indicated symptoms of pneumorrhachis manifesting immediately or within a few hours [6][7][8][9][10]. Our patient was an asymptomatic case of pneumorrhachis and pneumomediastinum detected two days following surgery.…”
Section: Discussionmentioning
confidence: 53%
“…Its presence in the postoperative period should prompt the clinician to look into the possible causes and rule out the life-threatening ones. To date, there have been only two cases of pneumomediastinum attributed to epidural block [ 6 , 7 ]. An incidental finding of pneumomediastinum two days after epidural analgesia has never been reported.…”
Section: Introductionmentioning
confidence: 99%